A Critical Study of the Book From Crisis to Collapse, Exploration of the Permanence or Collapse of Political Systems - Ebrahim Taheri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Revolutionary waves have always been a challenge to political systems. The culmination of these revolutions was in the twentieth century. In the 21st century, revolutions have become a serious challenge to the political systems of the Middle East and North Africa. To explain why and how the revolution took place, the general theories and models of the revolution have been presented by political scientists. This is especially true for sociologists of the revolution. Hossein Bashirieh, a former associate professor at the University of Tehran with a specialization in political sociology, is trying to provide general analytical models in this regard. The book From Crisis to Collapse: An Inquiry into the Persistence or Collapse of Political Systems is written with this approach in mind, which will be reviewed and criticized in this study. In this regard, a general introduction about the work and the author will be presented in the introduction. Then, in the second topic, in two separate domains, the formal and content aspects of the work are examined, and finally, in the third topic, with a critical approach, the formal and content shortcomings of the book are mentioned. Moreover, the conclusion is the final part of this article.